Determinan Emisi Karbondioksida (CO2): Studi Kasus Negara Kawasan ASEAN - F, Fahruddin; Qurrota A‘yun, Indanazulfa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
With increasing global concern over climate change, it is important to understand the factors influencing CO2 emissions in order to design effective environmental policies. Climate change is generally characterized by changes in climate conditions that can occur either directly or indirectly, which are influenced by various human activities such as in the industrial, economic, automotive sectors, as well as natural factors. This research analyzes the determinants of carbon dioxide (CO2) emissions in ASEAN countries. This study uses panel data from ten ASEAN countries during the 2012-2019 period. The panel data regression analysis method is used to evaluate the influence of variables such as forest area, energy consumption, population, motorbike use and Gross Domestic Product on CO2 emissions. The research results show that energy consumption and population are the main contributors to CO2 emissions in this region. These findings emphasize the need to implement sustainable energy policies and clean technologies to reduce CO2 emissions without hampering economic growth. It is hoped that this study can become a reference for policy makers in formulating climate change mitigation strategies in the ASEAN region.